Biological Variation of Corrected QT and QRS Electrocardiogram Intervals: Interpreting Results of Drug-induced Prolongation - Alan Wu; Kayla Kendric; Caitlin Roake; Emily Kelly (Western Journal of Emergency Medicine)
Introduction: Toxicologists use a universal threshold to determine QRS and QTc prolongation in poisoned patients. Further understanding of the biologic variance of these intervals may allow for a more personalized approach to assessing the clinical significance of electrocardiogram (ECG) changes in these patients. Methods: We recruited six male and six female healthy subjects. Standard 12-lead ECGs were performed in duplicate once per week for four consecutive weeks. We calculated the mean and standard deviation, the coefficient of variance (CV) for replicate readings (CV A), and within (CV I) and between individuals (CV G) using analysis of variance for all subjects and separately for males and females. From these measured parameters, we determined the index of individuality (II), the reference change value (RCV), and number of readings needed to maintain a homeostatic setpoint. Results: The median QRS interval for healthy males (103.4 milliseconds [ms]) was statistically higher than that for females (88.6 ms) in our study ( P < .05). The CV A and CV I for the QRS interval for the total cohort were relatively low at 3.0 and 2.2, respectively. The CV G for the QRS interval was relatively high at 12.9. There was no difference in the QTcorrected (QTc) interval between gender (404 vs 415 msec, respectively). The II was 0.29 for QRS and 0.74 for QTc in pooled subjects. The RCV was 10.3 and 7.1 msec, respectively, for QRS and QTc for all subjects. The number of samples needed to establish a homeostatic set point was 1 for all analyses at a closeness of 10% with a 95% probability ( P = .05). Conclusion: We demonstrated a significant difference in QRS duration between healthy males and females as well as a low II, particularly for the QRS interval, indicating that the CV G is greater than the CV I among these ECG intervals. In this study we also determined that one ECG is needed to establish a homeostatic set point for patients. If a baseline ECG is available, medical toxicologists would benefit from using the baseline tracing as an internal reference for determining QRS and QTc prolongation in the individual patient rather than a predetermined universal threshold for managing poisoned patients.